1975
DOI: 10.1126/science.188.4190.787
|View full text |Cite
|
Sign up to set email alerts
|

Magma Beneath Yellowstone National Park

Abstract: The Yellowstone plateau volcanic field is less than 2 million years old, lies in a region of intense tectonic and hydrothermal activity, and probably has the potential for further volcanic activity. The youngest of three volcanic cycles in the field climaxed 600,000 years ago with a voluminous ashflow eruption and the collapse of two contiguous cauldron blocks. Doming 150,000 years ago, followed by voluminous rhyolitic extrusions as recently as 70,000 years ago, and high convective heat flow at present indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(65 citation statements)
references
References 17 publications
1
64
0
Order By: Relevance
“…Yellowstone has been the site of extensive volcanism throughout the Cenozoic [51], with the geyser basins underlain entirely by Quaternary-age rhyolitic rocks [52]. Regional fault systems and the Yellowstone Caldera control the distribution of thermal features [53,54]. The entire area has been extensively glaciated, and many of the springs and geysers issue from stream and glacial sediments derived from the rhyolites [55].…”
Section: Yellowstone Wy Site (Active Geothermal System)mentioning
confidence: 99%
“…Yellowstone has been the site of extensive volcanism throughout the Cenozoic [51], with the geyser basins underlain entirely by Quaternary-age rhyolitic rocks [52]. Regional fault systems and the Yellowstone Caldera control the distribution of thermal features [53,54]. The entire area has been extensively glaciated, and many of the springs and geysers issue from stream and glacial sediments derived from the rhyolites [55].…”
Section: Yellowstone Wy Site (Active Geothermal System)mentioning
confidence: 99%
“…8). Geophysical methods that have claimed to have successfully detect extensive bodies of shallow magma elsewhere (e.g., Eaton et al 1975) have not demonstrated the existence of shallow magma bodies at Coso, but frequent seismicity (Walter and Weaver 1980), as well as teleseismic P-delay tomography studies (Reasenberg et al 1980;Wilson et al 2003), show evidence for a low-velocity body in the middle crust (top of the body at *5 km below the surface). Given that the volume of intrusive silicic magma at Coso may be as much as 100 times greater than the erupted volume ) the magma reservoir(s) may have been larger at certain times in the past.…”
Section: Coso Rhyolite Compositional Evolutionmentioning
confidence: 99%
“…Geochronology by Gansecki and others (1996) using fig. 41) with a well cemented diamicton overlying a bedded lacustrine unit (Christiansen and Blank, 1975;Richmond, 1976 fig. 41).…”
Section: Stop 14 Grand Canyon Of the Yellowstonementioning
confidence: 99%